Information needs and seeking behaviour of IT professionals in a multinational company. - Melwin Singaram. (2008)
The purpose of this dissertation was to investigate the perceptions of the importance of different information needs, frequency and reasons of using different information sources, their preferred information formats, frequency of sharing information, preferred modes of sharing information and the perceptions of barriers to information sharing within and with other departments.